Chronic myeloid leukemia: ESMO clinical practice guidelines for diagnosis, treatment and follow-up - Baccarani, Michele; Pileri, Stefano A.; Steegmann, J.-L.; Müller, Martin Christian; Soverini, S.; Dreyling, Martin (Annals of oncology, 2012)
The incidence of chronic myeloid leukemia (CML) ranges between 10 and 15 cases/106/year (age adjusted) without any major geographic or ethnic differences [1]. T